Structure characterization and anticoagulant activity of a novel polysaccharide from Leonurus artemisia (Laur.) S. Y. Hu F. Issue 4 (10th January 2020) - Hu, Cheng; Li, Hao-Xuan; Zhang, Meng-Ting; Liu, Li-Fang
Abstract : An acidic polysaccharide, denoted LAP-1 was extracted, isolated and purified from Leonurus artemisia (Laur.), in addition to its structure and anticoagulant activity were explored. Abstract : An acidic polysaccharide, named LAP-1, was extracted and isolated from Leonurus artemisia (Laur.), and was further purified with ion exchange chromatography and gel chromatography. The extraction conditions of the crude polysaccharides were optimized by single-factor experiments and response surface methodology. The primary structure of the purified polysaccharide was measured by FT-IR, GC-MS, and NMR. The results showed that LAP-1 was mainly composed of galacturonic acid (GalA), mannose (Man), xylose (Xyl), rhamnose (Rha), arabinose (Ara), glucose (Glc), galactose (Gal), fucose (Fuc), ribose (Rib), and glucuronic acid (GlcA) in the molar ratio of 8.74 : 3.45 : 1.02 : 1 : 2.11 : 5.60 : 4.73 : 1.08 : 1.09 : 1.47. Primary structure analysis results indicated that LAP-1 contained characteristic glycosyl linkages such as →1)-α-d -Man p, →1)-α-d -Glc p, →1)-α-d -Ara p -(2→, →1)-β-d -Gal p -(3→, →1)-β-d -Man p -(4→, →1)-β-d -Gal p -(4→, →1)-β-d -Glc p -(4→, →1)-β-d -GalA p -(4→, →1)-β-d -GlcA p -(4→, →1)-β-d -Man p -(4, 6→, →1)-β-d -Man p -(3, 4→. The M w / M n (PDI), M n, M z and M w of LAP-1 were determined to be 1.423, 6.979 × 10 3 g mol −1, 1.409 × 10 4 g mol −1, and 9.930 × 10 3 g mol −1 by HPSEC-MALLS-RID and DLS. SEM, TEM and AFM results indicated that LAP-1 was a highly branched structure. LAP-1 showed mild anticoagulant activity, low toxicity, and less spontaneous bleeding compared with heparin sodium. These results demonstrated the effective coagulation activity of Leonurus artemisia polysaccharides. Thus, the purified LAP-1 could be explored as a promising anticoagulant agent for the treatment of coagulation disorders.